CuO–SnO2 sensor for room-temperature CO detection: Experiments and DFT calculations - Wang, Weiqi; Cao, Jiamu; Wang, Shimin; Zhang, Rongji; Zhang, Yufeng (Sensors and actuators. B, Chemical, 2024)
Constructing heterostructures composed of different components is an emerging strategy to develop high–performance gas sensors with low operation temperatures, high sensitivity and reliable selectivity. Herein, a CuO–SnO2 sensor for ultra-sensitive CO detection at room temperature is designed. Gas sensing properties of CuO–SnO2 sensors are investigated with changing CO gas concentration, and each CuO–SnO2 sensor exhibits better sensing performances than SnO2 and CuO sensors. At 20 °C, the optimal CuO–SnO2 sensor has an excellent response of 39.56 % to 300 ppm CO gas with rapid response/recovery times (56/23 s), an ultralow detection limit of 159 ppb, and a high sensitivity of 0.127 % ppm−1. Additionally, the optimal CuO–SnO2 sensor exhibit good long-term stability, excellent reproductivity, and marked selectivity for CO molecules. The enhanced sensing mechanisms of the CuO–SnO2 heterostructure are attributed to the large specific surface area, abundant oxygen vacancies, and modulation effects of potential barrier created at the CuO–SnO2 heterojunction. Finally, first-principles calculations are implemented to investigate the adsorption ability and charge transfer of CO molecule on the CuO–SnO2 surface, further revealing the improved electron interactions between the CO molecule and CuO–SnO2 heterostructure at the molecular level. These new discoveries and insights aim to promote the research of heterostructures in chemical sensors through comprehensive theoretical and experimental studies. [Display omitted] •CuO–SnO2 heterostructures were prepared by the template sacrificial method.•CuO–SnO2 heterostructures exhibited an improved response to CO at room temperature.•DFT results show the enhanced adsorption effects of CuO–SnO2 heterostructures for CO.